Research on the Influence of Publicness Theory on Social Media Development in the New Era - Qin, Bolun (Pacific International Journal, 2025)
At present, technological development like the Internet and mobile devices has brought the traditional mass media model in human society into the era of interactive social media that is more in line with the original needs of human beings. Overall, how the theoretical basis of the publicness theory will guide the development of social media in the new era has become one of the main research topics. Amid digital era of new media, the complexity and diversity of information dissemination requires Marxist media theory to break through the boundaries of traditional disciplines, and enhance its adaptability through interdisciplinary cooperation. Interdisciplinary integration, particularly with information technology, sociology and psychology can equip Marxist media theory with new research methods and analytical tools.